THE EFFECT OF AUDIOBOOK USE ON EFL STUDENTSâ FLUENCY DEVELOPMENT - Ayunda, Achlia Niza (Journal on English as a Foreign Language (JEFL), 2013)
This article uncovered an empirical study of audiobook - a form of podcasting media. The subjects were two classes of 30 learners of English, fifteen of whom (one class) were randomly assigned to a meaning-focused input group using audiobooks and the other class to a non-audiobook group. There were two separated groups which were randomly assigned to a meaning-focused input group applying audiobooks and the other class to a non-audiobook group. This study implemented pretest and posttest research design. During one complete semester the subjects of experimental class accomplished fourteen pedagogical audiobook sessions while the control group were provided with another learning media.Â  Data collected consisted of orally in-pairs test performed by the subjects in both groups. Audiobooks appeared to be successful in this study in that they led to considerable improvement in fluency and vocabulary size consistency during oral performance.Keywords: audiobooks, meaning-focused input, L2, output, fluency, learning media